SOME THOUGHTS ON INTERNAL CONTROL SYSTEMS OF THE FIRM. - Zannetos, Zenon S. (The Accounting Review, 1964)
Abstract To summarize, we have initially examined the implications and short-comings of two important deterministic models, that of the classical theory of the firm and Taylor's model of rationalization of operations. We have shown that under theft assumptions, neither one necessitates any internal control systems, because the individuals are unconsciously influenced to allocate their efforts optimally. Then we have examined an alternative model that emphasizes conscious co-ordination of activities for the accomplishment of common objectives. The firm according to this model is viewed as a group of resources (people usually) that are brought together for the accomplishment of a common goal or an array of goals. These people are considered as willful agents with different degrees of rationality and capable of making value judgments. Consequently one cannot automatically assume that theft behavior is "optimizing," but must find ways of guaranteeing that the behavior of each and every one of these willful agents is consistent with the overall objective or objectives. That is one important place where the necessity of conscious co-ordination and control of activities enters. If people are left alone they will attempt to maximize what they perceive to be in their own best interest. If this happened to coincide with the interests of the firm well and good, otherwise the objectives of the firm are superseded by the interests of the individuals which may in themselves be conflicting. No one can honestly claim that a firm will succeed in enforcing an absolute identity between its goals and those of its employees. This problem is not unlike the one that has been plaguing the economists in their efforts toward maximizing social welfare. There is no doubt, however, that the firm can influence the direction as well as the magnitude of its employee's efforts. It would be quite disappointing, not only to managers but also to us as educators of managers, if we were to find out that managerial skills as well as complicated control systems can do nothing to change the particular behavior and range of rationality of an individual.